Exploring the Links between HIV/AIDS, Social Capital, and Development - David, Antonio C.; Li, Carmen A. (World Bank, Washington, DC, 2012)
This paper attempts to quantify the impact of the HIV/AIDS epidemic on social capital with cross-country data. Using data from the World Values Survey, the authors estimate reduced-form regressions of the main determinants of social capital controlling for HIV prevalence, institutional quality, social distance, and economic indicators. The results obtained indicate that HIV prevalence affects social capital negatively. The empirical estimates suggest that a one standard deviation increase in HIV prevalence will lead to a decline of at least 1 percent in trust, controlling for other determinants of social capital. Moving from a country with a relatively low level of HIV prevalence, such as Estonia, to a country with a relatively high level, such as Uganda, there is a more than 11 percent point decline in social capital. These results are robust in a number of dimensions and highlight the empirical importance of an additional mechanism through which HIV/AIDS hinders the development process.